Pendidikan Karakter dalam Perspektif Islam: Integrasi Nilai-Nilai Qur’ani dalam Praktik Pendidikan Sekolah - Anak Agung Sagung Oka Anggrena; Asti Melani Putri; Gusmaneli Gusmaneli (GLOBAL SCIENTS PUBLISHER, 2025)
Character education in Islam is very important to form a generation that has good morals and strong integrity, especially amidst the challenges of digitalization and globalization. The Qur'an as the main source of Islamic values ​​is the basis for character formation, emphasizing values ​​such as monotheism, honesty, responsibility, compassion, and hard work. The application of Qur'anic values ​​in the curriculum, school activities, and creating a supportive environment and role models from teachers are effective strategies in the process of internalizing Islamic character. Cooperation between schools, families, and communities also plays an important role in maintaining the consistency of the values ​​taught to students. With this comprehensive approach, Islamic character education can produce individuals who are not only intellectually intelligent, but also have spiritual and social strength.